A STUDY ON THE REPRESENTATION OF CHILDHOOD TRAUMA IN SHARANKUMAR LIMBALE’S THE OUTCASTE (2003) - Boddu, Kiran Kumar; N S, Prasantha Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The genre of autobiography unfolds the most important events of an individual’s life. Dalit autobiographies mostly document the childhood events of a dalit writer narrating in the context of social, economic, cultural and historical in which time he/she lives. Through the lens of dalit child we can understand the socio-economical, cultural conditions of the day. Therefore, the life of a dalit child becomes an integral part of dalit autobiography. It revolves in and around a dalit child narrating the successful and unsuccessful events of a dalit writer’s childhood. Mostly, highlighting the child’s emotional travails and tribulations that he and she undergoes during the time of childhood. So, childhood plays an important role especially in dalit’s life. Childhood decides the fate of a dalit person if he/she born into a dalit community. The present paper explores how the dalit writer’s childhood is interspersed with events that repeatedly impel him/her to raise ultimate question (regarding equality, oppression, untouchability etc.) which the society considers impossible.